Retrospective evaluation of ocular injuries in fractures of the zygomaticoorbital complex in a level I trauma center: is primary specialized ophthalmologic examination always necessary? - Kramer, Vanessa; Vounotrypidis, Efstathios; Steinkohl, Christian; Weiß, Christel; Schramm, Alexander; Wilde, Frank; Ebeling, Marcel; Sakkas, Andreas (International ophthalmology, 2025)
The necessity of a specialized ophthalmological assessment following fractures of the zygomaticoorbital (ZMO) complex in an emergency setting is still debated in resource-limited health systems. The primary aim of this study was to determine the incidence and types of ocular and periocular injuries (OPIs) associated with different fracture patterns of the ZMO complex. The secondary aim was to investigate the association between patient- and trauma-specific variables with the different types of OPI and identify high-risk patients for severe OPI.